Lyophilized Polyvinyl Alcohol and Chitosan Scaffolds Pre-Loaded with Silicon Dioxide Nanoparticles for Tissue Regeneration - Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Materials with a soft tissue regenerative capacity can be produced using biopolymer scaffolds and nanomaterials, which allow injured tissue to recover without any side effects or limitations. Four formulations were prepared using polyvinyl alcohol (PVA) and chitosan (CS), with silicon dioxide nanoparticles (NPs-SiO2) incorporated using the freeze-drying method at a temperature of −50 °C. TGA and DSC showed no change in thermal degradation, with glass transition temperatures around 74 °C and 77 °C. The interactions between the hydroxyl groups of PVA and CS remained stable. Scanning electron microscopy (SEM) indicated that the incorporation of NPs-SiO2 complemented the freeze-drying process, enabling the dispersion of the components on the polymeric matrix and obtaining structures with a small pore size (between 30 and 60 μm) and large pores (between 100 and 160 μm). The antimicrobial capacity analysis of Gram-positive and Gram-negative bacteria revealed that the scaffolds inhibited around 99% of K. pneumoniae, E. cloacae, and S. aureus ATCC 55804. The subdermal implantation analysis demonstrated tissue growth and proliferation, with good biocompatibility, promoting the healing process for tissue restoration through the simultaneous degradation and formation of type I collagen fibers. All the results presented expand the boundaries in tissue engineering and regenerative medicine by highlighting the crucial role of nanoparticles in optimizing scaffold properties. © 2024 by the authors.